Estimating the global impact of rotavirus vaccines on child mortality - Clark, Andrew; Mahmud, Sarwat; Debellut, Frederic; Pecenka, Clint; Jit, Mark; Perin, Jamie; Tate, Jacqueline; Soeters, Heidi M.; Black, Robert E.; Santosham, Mathuram; Sanderson, Colin (International journal of infectious diseases, 2023)
•Rotavirus vaccines prevented around 140,000 child deaths in the period 2006-2019.•Relaxing age restrictions prevented up to 17,000 deaths in the period 2013-2019.•Global use of rotavirus vaccines could prevent over one-third of rotavirus deaths. We estimated the global impact of rotavirus vaccines on deaths among children under five years old by year. We used a proportionate outcomes model with a finely disaggregated age structure to estimate rotavirus deaths prevented by vaccination over the period 2006-2019 in 186 countries. We ran deterministic and probabilistic uncertainty analyses and compared our estimates to surveillance-based estimates in 20 countries. We estimate that rotavirus vaccines prevented 139,000 under-five rotavirus deaths (95% uncertainty interval 98,000-201,000) in the period 2006-2019. In 2019 alone, rotavirus vaccines prevented 15% (95% uncertainty interval 11-21%) of under-five rotavirus deaths (0.5% of child mortality). Assuming global use of rotavirus vaccines and coverage equivalent to other co-administered vaccines could prevent 37% of under-five rotavirus deaths (1.2% of child mortality). Our estimates were sensitive to the choice of rotavirus mortality burden data and several vaccine impact modeling assumptions. The World Health Organization's recommendation to remove age restrictions in 2012 could have prevented up to 17,000 rotavirus deaths in the period 2013-2019. Our modeled estimates of rotavirus vaccine impact were broadly consistent with estimates from post-vaccination surveillance sites. Rotavirus vaccines have made a valuable contribution to global public health. Enhanced rotavirus mortality prevention strategies are needed in countries with high mortality in under-5-year-old children.